Prevention of mother-to-child transmission programme : how "informed" is the literate mother's decision regarding infant feeding options in the Gert Sibande district, Mpumalanga province, South Africa - Davis, Annemarie; Labadarios, D.; Marais, D.; Cotton, M. F. (Stellenbosch : University of Stellenbosch, 2010)
225 leaves printed on single pages, preliminary pages i- xxiii and numbered pages 1-203. Includes bibliography, list of abbreviations, list of definitions, list of tables and figures and list of appendices.